Scars of war : the politics of paternity and responsibility for the Amerasians of Vietnam - Thomas, Sabrina (Borderlands and transcultural studies., 2021)
Scars of War examines how the exclusion of mixed-race persons and people of Asian descent in the United States shaped the efforts of policymakers to recognize the Amerasians of Vietnam as American children and initiate legislation that designated them unfit for American citizenship.